Implementasi Ajaran Catur Paramita Di Panti Asuhan Dana Punia - Kadek Yuliana (Pramana: Jurnal Hasil Penelitian, 2023)
The purpose of making this article is to get to know, discover and understand more deeply the teachings of Catur Paramita at the Dana Punia Singaraja Orphanage. The method used to find out the teachings of Catur Paramita at the Dana Punia Singaraja Orphanage in this article is to use the literature review method. Catur Paramita are four virtuous attitudes of behavior consisting of Maitri, Karuna, Mudita and Upeksa. The discussion regarding the teachings of Catur Paramita at the Dana Punia Singaraja Orphanage shows that: 1) the environmental conditions of the Dana Punia Orphanage are the right target for implementing the teachings of Catur Paramita; 2) implementing the teachings of Catur Paramita is an obligation that is applied to the children of the Dana Punia Orphanage.